Involuntary emotional expression disorder in Alzheimer's disease : Psychopharmacotherapy aspects - Mimica, Ninoslav (Array, 2009)
Involuntary emotional expression disorder (IEED) is syndrome characterized with relatively stereotypical episodes of uncontrollable crying and/or laughing. IEED is very common but misdiagnosed and consequently undertreated. Prevalence of IEED in AD is between 15-39%. Recent controlled clinical studies suggest that dextromethorphan (DM) and quinidine (Q) is an effective treatment for IEED. United States Food and Drug Administration (FDA) has accepted for filing and review its New Drug Application (NDA) for ZenviaTM (dextromethorphan hydrobromide and quinidine sulfate capsules) for the treatment of IEED. In Republic of Croatia current treatment involves antidepressants (tricyclic and selective serotonin reuptake inhibitors), antipsychotic agents, anxiolytics, antidementives and mood stabilizers